2017
DOI: 10.5152/jarem.2017.1178
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Factors Affecting Continence after Robotic Radical Prostatectomy

Abstract: ÖZAmaç: Bu çalışma ile prostat kanseri nedeniyle robot yardımlı radikal prostatektomi yapılan hastalarda kontinansı etkileyen faktörleri değer-lendirmeyi amaçladık. Yöntemler: Ağustos 2009 -Ocak 2014 tarihleri arasında Bakırköy Dr. Sadi Konuk Eğitim ve Araştırma Hastanesi Üroloji Kliniğinde prostat kanseri nedeniyle Robot yardımlı laparaskopik radikal prostatektomi uygulanan 385 hastanın verileri retrospektif olarak incelendi. Bulgular: Preop Uluslararası Erektil İşlev İndexi (IIEF) skoru ≥22 olanlar ile D'Ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The authors reported that PSA below 10 ng/ mL and age younger than 60 were correlated with favorable early functional outcomes (22). On the other hand, Torer et al (23) found that preoperative serum PSA and Gleason score did not affect continence in 385 patients operated for RALRP. In our study, we found no significant difference in PSA level between patients with and without postoperative urinary incontinence.…”
Section: Discussionmentioning
confidence: 98%
“…The authors reported that PSA below 10 ng/ mL and age younger than 60 were correlated with favorable early functional outcomes (22). On the other hand, Torer et al (23) found that preoperative serum PSA and Gleason score did not affect continence in 385 patients operated for RALRP. In our study, we found no significant difference in PSA level between patients with and without postoperative urinary incontinence.…”
Section: Discussionmentioning
confidence: 98%
“…Robotic surgery has gained significant popularity within the last decade and included in the daily practice of urology (6,7,8,9). Also in our country, robotic surgery is widely used and series with high number of patients are contributing to the literature (10,11). In series with follow-up periods longer than five years, it was determined that there was no difference between open surgery and robotic surgery in terms of oncological results after radical prostatectomy, radical cystectomy and partial nephrectomy (12,13,14).…”
Section: Discussionmentioning
confidence: 99%